Analisis histopatologi insang ikan belanak Mugil cephalus hasil tangkapan nelayan di Wilayah Bumi Dipasena Mulya, Kabupaten Tulang Bawang, Lampung - Noor, Huriyatul Fitriyah; Putriani, Rizha Bery; Viani, Dwi Okta; Fikriawan, Akmal (Jurnal Sumberdaya Akuatik Indopasifik, 2025)
This research was conducted in Bumi Dipasena Mulya, East Rawajitu District, Tulangbawang Regency, Lampung, which is known for its intensive farming and fishing activities, especially mullet fish. The research method used is experimental, by measuring physico-chemical parameters of waters including temperature, salinity, pH and dissolved oxygen (DO). The results of the study showed the average value of several histopathological indicators for mullet fish, namely endema on the gills (3), which indicates swelling of the gill tissue due to fluid accumulation in response to environmental stress, such as pollution. In addition, the necrosis value (1,08) reflects the death of cells in the gill tissue, which is caused by exposure to harmful substances, including heavy metals, which can damage gill function. Congestion (1,92) indicates a buildup of blood in the gill vasculature, associated with an inflammatory or stress response, which can disrupt blood and oxygen flow. These findings emphasize the importance of water quality management to maintain the health of aquatic biota.